Սանահինի արքայական-իշխանական հանգստարանները Զաքարյանների տապանատան հնագիտական պեղումների համապատկերում - Նալբանդյան, Արման; Միրիջանյան, Դիանա
The desire of Armenian princes and kings to find the last rest in their native possessions is expressed by a number of facts. The royal and princely houses had their own spiritual centers, where the representatives of these houses were buried. While before the construction of vestibules (gavit‘) privileged persons were buried in the courtyards of churches (Tat‘ew, Vahanavank‘, Noravank‘), after the appearance of gavit‘s they also became burial places of clerics and secular nobility. In 979, when the Sanahin Monastery was proclaimed episcopal see by the decree of King Smbat II of Armenia, it also became the spiritual center of the Kyurikian kingdom. Therefore, it is no coincidence that the desire of the Kyurikian princes was to enjoy the patronage of Sanahin after their death. The famous sepulcher of the Zak‘arians is located outside the walled part of the complex, about 60 meters southeast of the central group of monuments, to the west of the St. Hakob Church. As part of the archaeological research of the sepulcher and the other structures of the southeastern group of monuments, in 2019 the St. Hakob Church and the Holy Resurrection Church, and in 2021–2022 the territory adjacent to the family sepulchre of the Zak‘arians with the section of the road leading to the complex were excavated. The research and excavations carried out in the territory of the sepulcher of the Zak‘arians gave significant results both in terms of dating the construction horizons and clarifying the cultural layers. Армянские князья и цари стремились обрести вечный покой в родных владениях, поэтому царские и княжеские дома имели свои духовные центры, где хоронили представителей своих династий. Если до постройки притворов знать хоронили во дворах церквей (Татев, Ваганаванк, Нораванк), то с их появлением они стали местами захоронения как духовной, так и светской знати. В 979 году, когда Смбат Патриарх провозгласил монастырь Санаин епископским престолом, он стал духовным центром царства Кюрикянов. Поэтому неслучайно желание князей Кюрикян пользоваться покровительством Санаина даже после смерти. Знаменитая гробница Закарянов находится за пределами обнесенной стеной части комплекса, примерно в 60-и м к юго-востоку от центральной группы памятников, к западу от церкви Св. Акопа. Во время археологических исследований гробницы и других сооружений на юго-востоке памятника в 2019 году были раскопаны церкви Св. Акопа, Св. Воскресения, а в 2021-2022 гг. – территория, прилегающая к родовой гробнице Закарянов и участок дороги, ведущий к комплексу памятников. Исследования и раскопки, проведенные в районе гробницы Закарянов, дали значительные результаты в плане датировки рабочих горизонтов и уточнения культурных слоев.
Keywords: Հնագիտություն